Pengaruh Pengetahuan Pajak, Sanksi Pajak, dan Tingkat Kepercayaan kepada Pemerintah terhadap Kepatuhan dalam Membayar Pajak Bumi dan Bangunan - Ristamada, Agea Ristiva; Purwatiningsih, Purwatiningsih (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study investigates the factors influencing taxpayer compliance in paying Land and Building Tax (Pajak Bumi dan Bangunan/PBB) in Pamulang District. Taxpayer compliance plays a crucial role in the effectiveness of tax collection and national development funding. However, compliance remains a challenge in various regions, including Pamulang. Several factors may influence compliance, including the level of tax knowledge, the presence of tax sanctions, and trust in the government. Understanding how these factors affect taxpayer behavior is essential for improving local tax revenues. This research employs a quantitative approach using a survey method. Data were gathered through a structured questionnaire distributed to 100 respondents selected using purposive sampling. The criteria for selection included individual taxpayers who are registered and active in paying Land and Building Tax. The data were analyzed using multiple linear regression to examine the relationship between the independent variables (tax knowledge, tax sanctions, and trust in the government) and the dependent variable (taxpayer compliance). The results show that, simultaneously, tax knowledge, tax sanctions, and trust in the government have a significant effect on taxpayer compliance. However, in partial analysis, only tax knowledge and tax sanctions have a statistically significant positive impact on compliance. Trust in the government does not show a significant individual effect, suggesting that informational and enforcement measures may play a more critical role than perceived trust.